Brian Cherney’s Illuminations - Adamcyk, David (Intersections, 2017)
Brian Cherney’s Illuminations for string orchestra, composed in 1987, reflects ideas related to Jewish mysticism. Descriptions and accounts of meditation techniques that ultimately lead to visions of light, and even an encounter with the divine, so inspired the composer that he decided to write a piece that re-enacts a meditative cycle. Illuminations is thus a dramatic staging: the listener, as if granted special insight into the mind of someone who is meditating, witnesses how the mind is transformed as it approaches light (or the divine). The composition expresses light and the divine in multiple ways, from the layout of the instruments on stage, to the formal plan of the piece, to the variety of pitch collections heard throughout the work. This article unveils some of the subtle intricacies that make Illuminations so powerfully evocative, and why it remains one of Cherney’s signal achievements.